Dynamic capabilities and survival of startup firms - Espinoza Pazos, Fernando (2023)
Startups provide benefits to countries because of their capacity to promote economic and social development. Nevertheless, startups face great challenges to survive, especially in the Peruvian context wherein they have limited capacity for innovation and a lack of organizational resources. Thus, this paper discusses why the obtention of ordinary organizational resources (e.g., the founder’s professional experience and entrepreneurial team networks) and the development of dynamic capabilities (e.g., the ability to learn from imitating business models and the capacity to adapt products and processes to target customers) are urgently needed for the survival of Peruvian startups and explains the distinction between these organizational resources and capabilities. Furthermore, recommendations for entrepreneurs in this regard are outlined in the conclusion.